Uji Kelayakan Perangkat Pembelajaran Pengelolaan Limbah dengan Pendekatan TASC (Thinking Actively In a Social Context) - Irsad Rosidi (SEJ (Science Education Journal), 2017)
Learning resources about waste management have been developed using Thinking Actively in a Social Context (TASC) approach. This research aimed to ascertain the feasibility of syllabus, lesson plans and students’ worksheet. The data was analyzed descriptively using feasibility test of expert judgement. The result showed that feasibility of silaby is 4,11 (“feasible” category); feasibility of lesson plans is 4,18 (“feasible” category); feasibility of students’ worksheet is 4,17 (“feasible” category). In conclusion, learning resources using TASC approach addressed for waste management topic is feasible to be implemented in the learning process.